2011
DOI: 10.1111/j.1744-6163.2011.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

An American and Dutch Partnership for Psychiatric Mental Health Advance Nursing Practice: Nurturing a Relationship Across the Ocean

Abstract: International partnerships within PMH advanced practice nursing promotes sharing of knowledge and solutions as patients and diseases have no border.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Her impact on the mental health facility promoted an environment of sharing problems and solutions. An article by Maas, Ezeobele, and Tetteroo (2012) described the development of an international psychiatric mental health partnership between the Netherlands and the United States (US). This article revealed the value of international nursing visitors to discuss and share knowledge and other perspectives on PMH nursing.…”
Section: International Nursing Exchanges In Mental Healthmentioning
confidence: 99%
“…Her impact on the mental health facility promoted an environment of sharing problems and solutions. An article by Maas, Ezeobele, and Tetteroo (2012) described the development of an international psychiatric mental health partnership between the Netherlands and the United States (US). This article revealed the value of international nursing visitors to discuss and share knowledge and other perspectives on PMH nursing.…”
Section: International Nursing Exchanges In Mental Healthmentioning
confidence: 99%
“…There is a dearth of literature about NP global exchanges. Maas et al (2012) identify that they teach one of the few NP curriculums that has an international experience, which is mandatory for their students. They suggest these opportunities for NP students promote a sharing of knowledge and problem solving as patient presentations and disease progression have "no border".…”
Section: Global Exchangesmentioning
confidence: 99%
“…There is a dearth of literature about NP global exchanges. Maas et al (2012) identify that they teach one of the few NP curriculums that has an international experience, which is mandatory for their students. They suggest that these opportunities for NP students promote a sharing of knowledge and problem solving as patient presentations and disease progression have “no border.” Global exchanges are a unique opportunity for NPs to think outside of their own culture and health care and recognize the similarities and differences of the role in another country (Maas et al, 2012).…”
Section: Global Exchangesmentioning
confidence: 99%
See 1 more Smart Citation
“…Jie, Andreatta, Liping, and Sijian (2010) found that immersion for student nurses experiencing an international perspective facilitates their personal and professional growth and allows them to understand different cultures and global issues. International experiences provide students an awareness of global nursing issues (Berland, Richards, & Lund, 2010;Maas, Ezeobele, & Tetteroo, 2012;Smith & Curry, 2011;Wright, 2010;Wros & Archer, 2010). In a systematic review of 23 empirical articles about international student exchange experiences, Kulbok, Mitchell, Glick, and Greiner (2012) found that there were few articles describing two-way exchange experiences in global nursing education and that there was not a model for best practice for international student clinical immersion exchanges.…”
mentioning
confidence: 99%